Circularly Polarised Luminescence in Enantiopure Samarium and Europium Cryptates. Issue 51 (20th August 2018) - Kreidt, Elisabeth; Arrico, Lorenzo; Zinna, Francesco; Di Bari, Lorenzo; Seitz, Michael
Abstract: Circularly polarised luminescence (CPL) is a chiroptical phenomenon gaining more and more attention, as the availability of the necessary spectrometers is getting better and first applications in bioimaging or for the preparation of OLEDs (organic light emitting diodes) are coming within range. Until now most examples of distinctly CPL‐active compounds were europium and terbium complexes though theoretically the electronic structure of samarium should be as suitable as the one of terbium. This discrepancy can be accounted for by the high susceptibility of samarium to non‐radiative deactivation processes. The aim of this study was to strategically circumvent this difficulty by the use of a ligand scaffold which has already proven to efficiently suppress these processes, namely the cryptates. The prepared partly deuterated samarium and europium complexes exhibit distinct circularly polarised luminescence with dissymmetry factors up to g lum =+0.13 (Sm III ) or g lum =−0.19 (Eu III ). Abstract : In an enantiopure cryptate scaffold designed to control nonradiative deactivation processes, Sm III exhibits distinct circularly polarised luminescence activity in the same order of magnitude as the corresponding Eu III compound.